In vitro antimicrobial susceptibility of clinical isolates from adult and paediatric patients in Jordan: Antimicrobial Testing Leadership and Surveillance (ATLAS) 2010–2021 - Al Jammal, Dima; Bachir, Julia; Moussa, Jihane A.; Al Ramahi, Jamal Wadi (Frontiers in Antibiotics, 2024)
Objectives: To evaluate the in vitro antimicrobial susceptibilities of Gram-positive and Gram-negative isolates from patients in Jordan between 2010 and 2021, through the Antimicrobial Testing Leadership and Surveillance (ATLAS) programme. Methods: Medical centres in Jordan collected bacterial isolates from hospitalised patients with defined infection sources between 2010 and 2021 (no isolates collected in 2014). Antimicrobial susceptibility was interpreted using CLSI standards. FDA-approved breakpoints were applied for tigecycline. The identification of β-lactamase genes was performed for a proportion of isolates using multiplex PCR assays. Results: More than 92% of Acinetobacter baumannii collected were multidrug-resistant (MDR) and/or carbapenem-resistant (CR), and > 50% susceptibility was reported only to minocycline (62.2% among both MDR and CR isolates). Rates of MDR and CR Pseudomonas aeruginosa were 14.3% and 20.5%, respectively, and among all P. aeruginosa collected from adults, susceptibility to ceftazidime/avibactam was 95.3% and to ceftolozane/tazobactam was 88.4%. For Escherichia coli from adults and MDR E. coli, susceptibility to ceftazidime/avibactam, ceftolozane/tazobactam, imipenem, meropenem and meropenem/vaborbactam was 92.1%–98.7%. Susceptibility to tigecycline was > 94% among Klebsiella pneumoniae from adult, paediatric, and ICU patients (all ages). CTX-M-15 was the most frequently identified β-lactamase gene among E. coli and K. pneumoniae. Susceptibility to most antimicrobial agents was < 50% among K. pneumoniae carrying CTX-M-15, CTX-M-9-type, NDM-5, and/or OXA-48 β-lactamase genes. All S. aureus collected were susceptible to teicoplanin, vancomycin, daptomycin, linezolid and tigecycline, with 96.1% of S. aureus from adults were susceptible to ceftaroline. Overall, 58.8% of Staphylococcus aureus were MRSA. Conclusions: This study provides valuable information regarding antimicrobial susceptibility in Jordan between 2010 and 2021. Continued monitoring of in vitro antimicrobial susceptibility is critical in the fight against antimicrobial resistance.